Influence of Feeding Cowpea (Vigna unguiculata) Leaves on the Performance of Vanaraja Laying Hen - Swain, Bijaya Kumar (Indian Journal of Animal Nutrition, 2018)
The study was undertaken to investigate the utilization of cow pea leaves in Vanaraja laying hens. Vanaraja laying hens (N=36, 25 weeks old)Â  were randomly distributed into 3 equal groups (duplicated into 3 groups of 3 laying hens each ) on wire mesh floored cages and offered standard layer ration @ 125g/hen/day (T1), standard layer ration @75g/hen/day and cow pea leaves as fresh basis @ 75g/hen/day (T2) and standard layer ration @ 62.5g/hen/day with cow pea leaves @ 125g/hen/day (T3) for a period of 8 weeks. Results indicated that significant (P